Bending vibration of beam elements under moving loads with considering vehicle braking forces - Nguyen Xuan Toan (Vietnam Journal of Mechanics, 2011)
The study of fluctuations of structures in general and bridge structures in particular under the influence of moving loads considering the impact of vehicle braking forces draws the attention of many scientists. However, due to the complexity of this problem a static method has been so far applied for approximate calculation in bridge design standards. In this article the author introduces the equation of bending vibrations of beam elements according to the model of dynamic interaction between beam elements and moving vehicle loads considering vehicle braking forces.